IMPLEMENTASI KEBIJAKAN PENGEMBANGAN KAPASITAS APARATUR PEMERINTAH KAMPUNG NAFRI DI DISTRIK ABEPURA KOTA JAYAPURA - Vera Misye Merahabia; Vince Tebay (Universitas Cenderawasih, 2022)
This article discusses the Implementation of capacity building policies for the village apparatus in the Abepura District, Kota Jayapura. Policy Implementation in principle is a way for a policy to achieve its goals. The purpose of this study is to analize the implementation of capacity building policies for the village apparatus later as government administrators. The type of research used in this study used a qualitative method, the focus of this research was on developing the capacity of the village government apparatus by using Implementation theory according to Merilee S. Grindle. The development of the apparatus capacity in the village of Nafri has not been carried out by the village government because it has not been budgeted for in the RKPKampung. So far, the village government has only implemented local government program through the related OPD by participating in training held by the relevant Office. Not all village officials were involved in training activities, only the village head, village secretary, and treasurer. This resulted in a lack of professionalism of the apparatus in carrying out their duties and functions in the village government, both in carrying out village administration and village financial management. Factors that influence the implementation of policies as well as the efforts made to implement the policy of developing the capacity of the apparatus in the village of Nafri, namely by increasing abilities in the field of work, increasing insight and knowledge, talents and potential, personality and work motives, and capital and work ethic.